Rozwiąż równania.
1.2(x+3)=10
2.3(x-1)+2=8
3.2(13-x)-9=1
4.3(1-x)+2=-7
5.3(x+3)=2(x+4)+x+1
6.4(3x+2)+5(2x+3)=-(2x+13)
7.4(x-2)=2(2x-1)+6(x+1)
8.2(x-2)-2(x-4)=5(x+1)-3x
9.7(y+3)=5y+2+2y
10.0,2x+0,3=1,3
11.5x-0,8=0,1+2x
12.8x-0,2=8x-0,1
13.0,01x+17=-0,16x
14,0,07(10x-1)=0,3x
15.0,83+0,82=0,23x+1,52
16.0,6x+2(0,1x-0,1)=0,2(x+1)
17.0,7(x+2)=0,4(x+1)+0,3x+1
18.0,1(2x+4)=2(1,3+0,3x)-0,6
19.0,1(2x+4)=2(1,3+0,3x)-0,6
20.0,1(x+1)-0,05(3x-10)=0,4-0,3x
21.-a-2(a-1)=-4(a-2)

1

Odpowiedzi

2010-03-04T18:50:59+01:00
1.2(x+3)=10
2x+6=10
2x=10-6
2x=4 /:2
x=2

2.3(x-1)+2=8
3x-3+2=8
3x-1=8
3x=8+1
3x=9 /:3
x=3

3.2(13-x)-9=1
26-2x-9=1
-2x=1-26+9
-2x=-16 /:(-2)
x=8

4.3(1-x)+2=-7
3-3x+2=-7
-3x+5=-7
-3x=-7-5
-3x=-12 /(-3)
x=4

5.3(x+3)=2(x+4)+x+1
3x+9=2x+8+x+1
3x-2x-x=8+1-9
0=0


6.4(3x+2)+5(2x+3)=-(2x+13)
12x+8+10x+15=-2x-13
22x+2x=-13-8-15
24x=36 /:24
x=36/24
x=6/4
x=3/2

7.4(x-2)=2(2x-1)+6(x+1)
4x-8=2x-2+6x+6
4x-2x-6x=6-2+8
-4x=12 /:(-4)
x=-3

8.2(x-2)-2(x-4)=5(x+1)-3x
2x-4-2x+8=5x+5-3x
-5x+3x=5+4-8
-2x=1 /:(-2)
x=-1/2

9.7(y+3)=5y+21+2y
7y+21=5y+2+2y
7y-5y-2y=21-21
0=0

10.0,2x+0,3=1,3
0,2x=1,3-0,3
0,2x=1 /:0,2
x=5


11.5x-0,8=0,1+2x
5x-2x=0,1+0,8
3x=0,9 /:3
x=0,3


12.8x-0,2=8x-0,1
8x-8x=-0,1+0,2
0=0,1


13.0,01x+17=-0,16x
0,01x+0,16x=-17
0,017x=-17 /:0,17
x=100

14)0,07(10x-1)=0,3x
0,7x-0,07=0,3x
0,7x-0,3x=0,07
0,4x=0,07 /:0,4
x=0,175

15.0,83+0,82=0,23x+1,52
1,65-1,52=0,23x
0,23x=0,13 /:0,23
x=0,6

16.0,6x+2(0,1x-0,1)=0,2(x+1)
0,6x+0,2x-0,2=0,2x+0,2
0,6x+0,2x-0,2x=0,2+0,2
0,6x=0,4 /:0,6
x=0,6

17.0,7(x+2)=0,4(x+1)+0,3x+1
0,7x+1,4=0,4x+0,4+0,3x+1
0,7x-0,4x-0,3x=0,4+1-1,4
0=-1

18.0,1(2x+4)=2(1,3+0,3x)-0,6
0,2x+0,4=2,6+0,6x-0,6
0,2x-0,6x=2,6-0,6-0,4
-0,4x=1,6 /(-0,4)
x=-4


19.0,1(2x+4)=2(1,3+0,3x)-0,6
0,2x+0,4=2,6+0,6x-0,6
0,2x-0,6x=2,6-0,6-0,4
-0,4x=1,6 /(-0,4)
x=-4

20.0,1(x+1)-0,05(3x-10)=0,4-0,3x
0,1x+0,1-0,15x+0,5=0,4-0,3x
0,1x-0,15x+0,3x=0,4-0,1-0,5
0,25x=-0,2 /:0,25
x=-0,8

21.-a-2(a-1)=-4(a-2)
-a-2a+2=-4a+8
-a-2a+4a=8-2
a=6